Disminución de pérdidas en el alimentador 3 de la subestación Salcedo mediante la ubicación de almacenadores de energía. - Ocapana Catota, Maximo Estalin (2020)
The electric power service is provided by distribution companies, domestically they are in charge of supplying the electrical service, maintaining continuity and reliability of electricity to consumers. This project is focused on the improvement of the use of electric feeders since their utility is at one hundred percent of its capacity at peak hours, being oversized the rest of the time, therefore an alternative is proposed that allows reducing power losses by introducing an energy storage system in the most critical points, serving as a backup of electrical energy. Besides, the population growth is reflected in the electrical systems with an increase in the load, which requires that the capacity of the systems grow proportionally. According to the information obtained from the thesis “ANÁLISIS DEL NIVEL DE VOLTAJE DEL ALIMENTADOR (SALCEDO – CENTRO), DE LA SUBESTACIÓN SALCEDO”, the Power Electrical System was modeled in the POWER FACTORY Software, which allowed to simulate scenarios with consumption values at peak hours, showing that the distribution and transformation elements are at their maximum capacity at a specific time..